Symposium of Materials Science and Chemistry III Selected, peer-reviewed papers from the 6th International Conference on Science and Technology (ICST 2020), September 7-8, 2020, Yogyakarta, Indonesia - Kusumaatmaja, Ahmad; Wahyuningsih, Tutik Dwi; Khairuddean, Melati; Kartini, Indriana; Roto, Roto; Ohto, Keisuke; Siswanta, Dwi; Motuzas, Julius; Natsir, Taufik Abdillah (Key Engineering Materials Ser., 2021)
Selected peer-reviewed full text papers from the 6th International Conference on Science and Technology (ICST 2020) Selected, peer-reviewed papers from the 6th International Conference on Science and Technology (ICST 2020), September 7-8, 2020, Yogyakarta, Indonesia.